Highly Specific, Single‐step Cancer Cell Isolation with Multi‐Aptamer‐Mediated Proximity Ligation on Live Cell Membranes. Issue 52 (15th October 2020) - Gao, Qianqian; Zhao, Yumeng; Xu, Kangli; Zhang, Chao; Ma, Qian; Qi, Liqing; Chao, Dandan; Zheng, Tingting; Yang, Linlin; Miao, Yanyan; Han, Da
Abstract: A single‐step method for isolation of specific cells based on multiple surface markers will have unique advantages because of its scalability, efficacy, and mildness. Herein, we developed multi‐aptamer‐mediated proximity ligation method on live cell membranes that leverages a multi‐receptor co‐recognition design for enhanced specificity, as well as a robust in situ signal amplification design for improved sensitivity of cell isolation. We demonstrated the promising efficacy of our method on differentiating tumor cell subtypes in both cell mixtures and clinical samples. Owing to its simple and fast operation with excellent cell isolation sensitivity and accuracy, this approach will have broad applications in biological science, biomedical engineering, and personalized medicine. Abstract : A multi‐aptamer‐mediated proximity ligation method on live cell membranes with enhanced specificity and improved sensitivity for cell isolation was developed. The promising efficacy on differentiating tumor cell subtypes in both cell mixtures and clinical samples shows the great promise of this method for cancer diagnosis.